(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The process of globalization reduces the importance of inter-State, intercultural and inter-societal boundaries, forming a global standard cultural society. This process encourages adolescents to perceive and realize national values, patriotism, civic responsibility and territorial identity - characteristics that distinguish them from other peoples and states - as standard universal values. This article examines such factors influencing the identification of adolescents in Kyrgyz society as family, educational environment, social circle in free time and social networks. The analysis of these factors makes it possible to trace the identification process of adolescents in a globalizing society. In conclusion, it can be said that Kyrgyz society, being under the influence of globalization, is undergoing changes, which is especially evident during the age crisis of adolescents. During this period, their view of the world expands, their attachment to the family weakens, and the circle of communication with peers becomes more active and significant. It is important that the space in which an adolescent’s identity is formed, whether real or virtual, be filled with symbolic signs of national identity that evoke positive images and leave a positive trace in his or her memory.